Women as Social Media Entrepreneurs in Indonesia - A. Rahmawati; A. Kusuma; Sumardjijati (Future Science)
The numbers of women entrepreneurs have been growing significantly in recent years, however, such a phenomenon is severely under-research in comparison to male entrepreneurship. This paper attempts to fill the lacuna of this scholarship by researching the background and motivations women doing business in Indonesia. Twenty women entrepreneurs in Surabaya were interviewed individually as well as in groups. In-depth interviews and focus group discussions were generated to investigate, firstly motivations behind Indonesian women entrepreneurs to start their business endeavors. And secondly, how to do social media and digital technology advance women entrepreneurship. The paper concludes that overall the motivations behind women doing business are mainly to pursue their passion and creativity. This is especially prevalent in women in creative industry entrepreneurs such as fashion, craft and culinary. Secondly, women own business to continue the already established family legacy and thirdly, out of necessity to support the family. The findings also suggested that social media has its own benefits and disadvantages. Participants stated that the mobility and interactivity factors are the crucial benefits of social media while also listed restlessness and competitiveness as its disadvantages.